2006
DOI: 10.1038/modpathol.3800569
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis of immunohistochemical profiles in synovial sarcoma, malignant peripheral nerve sheath tumor, and Ewing sarcoma

Abstract: As a result of overlapping morphologic and immunohistochemical features, it can be difficult to distinguish synovial sarcoma, malignant peripheral nerve sheath tumor, and Ewing sarcoma/primitive neuroectodermal tumor in core biopsies. To analyze and compare immunohistochemical profiles, we stained tissue microarrays of 23 synovial sarcomas, 23 malignant peripheral nerve sheath tumors, and 27 Ewing sarcomas with 22 antibodies potentially useful in the differential diagnosis, and analyzed the data with cluster a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
111
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(121 citation statements)
references
References 37 publications
6
111
2
2
Order By: Relevance
“…It is frequently used to analyze mRNA expression profiles of thousands of genes in DNA microarray studies. In recent years, this statistical tool has been applied to analyze immunohistochemical results on Formalinfixed paraffin-embedded tissues using multiple antibodies, and has demonstrated that tumors clustered into groups that correlated to their site of origin, 23 phenotype, 24,25 biologic potential, 26 and prognosis. [27][28][29] Our goal was to identify a cluster of markers that can be used in combination in a diagnostic immunohistochemical panel for differentiating adenoid cystic carcinoma from polymorphous low-grade adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…It is frequently used to analyze mRNA expression profiles of thousands of genes in DNA microarray studies. In recent years, this statistical tool has been applied to analyze immunohistochemical results on Formalinfixed paraffin-embedded tissues using multiple antibodies, and has demonstrated that tumors clustered into groups that correlated to their site of origin, 23 phenotype, 24,25 biologic potential, 26 and prognosis. [27][28][29] Our goal was to identify a cluster of markers that can be used in combination in a diagnostic immunohistochemical panel for differentiating adenoid cystic carcinoma from polymorphous low-grade adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Olsen et al 18 performed a cluster analysis of the immunohistochemical profiles in RT-PCR proven cases of SS and concluded that EMA (sensitivity 91%) was the single most sensitive and specific marker that was positive in both bi and monophasic variants. Hence, for the retrospective analysis, we selected 16 cases (of the initial 20), which, on ICC, were positive for vimentin and epithelial membrane antigen or cytokeratin.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent analysis, the most useful marker of SS was epithelial membrane antigen rather than cytokeratin. 18 Among the cytokeratins, CK7 is more specific for SS. 18 In addition S-100, NSE, synaptophysin, and CD34 may be applied to distinguish the sarcomas listed above.…”
Section: Discussionmentioning
confidence: 99%
“…However, each of these markers can be expressed in a variety of other tumors. A recent study 20 used cluster analysis to analyze immunohistochemical data obtained from a tissue microarray of 73 soft tissue tumors (23 synovial sarcoma, 23 malignant peripheral nerve sheath tumor and 27 Ewing/PNET) with 22 different antibodies, including cytokeratin, CD99, EMA and bcl-2. The data suggested two clusters among synovial sarcoma, one cluster (n ¼ 11) was cytokeratin and EMA positive and another (n ¼ 9) was cytokeratin negative, but EMA, bcl-2 and mostly CD56 positive.…”
Section: Discussionmentioning
confidence: 99%
“…The study also highlighted aberrant staining reactions and diagnostic pitfalls in these tumors. 20 We believe the use of practical immunostaining assay for the SYT detection is likely to decrease the number of cases requiring large battery of studies for precise diagnosis of synovial sarcoma. If the staining shows an equivocal results or the case is histologically suspicious for a lesion other than synovial sarcoma such as a malignant peripheral nerve sheath tumor, various ancillary studies including molecular assays and electron microscopy could be performed as usual for further work-up.…”
Section: Discussionmentioning
confidence: 99%